2009
DOI: 10.1002/mds.22747
|View full text |Cite
|
Sign up to set email alerts
|

Relative preservation of thalamic centromedian nucleus in parkinsonian patients with dystonia

Abstract: To determine whether variable thalamic degeneration in Parkinson's disease (PD) contributes to less drug responsive clinical features. Formalin-fixed thalami from longitudinally followed patients with PD and early dystonia (N = 6), early falls (N = 5) or no dystonia or falls (N = 6) and age-matched controls without neuropathology (N = 10) were serially sectioned, stained, and analyzed. Neurons in the centromedian parafascicular (CM-Pf) nucleus were quantified using the optical disector method and analysis of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
(65 reference statements)
0
7
0
1
Order By: Relevance
“…Decreased basal ganglia function, from both overt damage to the caudal intralaminar thalamus (projects to the basal ganglia where terminal amyloid‐β plaque deposition was observed) and nigral inclusion bodies (correlate with decreased striatal dopamine production) [14], would appear to be significant. It is of interest that cell loss in the caudal intralaminar thalamus has been observed previously in patients with Parkinson's disease and early dystonia [15], but perhaps the cerebellar pathology may be more important for the symptoms observed. Animal models show that restricted Purkinje cell abnormalities are sufficient to cause dystonia [16], although dystonia was not a feature in our patient, but is prominent in subsequent generations.…”
mentioning
confidence: 80%
“…Decreased basal ganglia function, from both overt damage to the caudal intralaminar thalamus (projects to the basal ganglia where terminal amyloid‐β plaque deposition was observed) and nigral inclusion bodies (correlate with decreased striatal dopamine production) [14], would appear to be significant. It is of interest that cell loss in the caudal intralaminar thalamus has been observed previously in patients with Parkinson's disease and early dystonia [15], but perhaps the cerebellar pathology may be more important for the symptoms observed. Animal models show that restricted Purkinje cell abnormalities are sufficient to cause dystonia [16], although dystonia was not a feature in our patient, but is prominent in subsequent generations.…”
mentioning
confidence: 80%
“…This classic view assumes that there is no structural damage to the thalamus itself. However, more recently, several studies revealed that the thalamus is one of select targets of extranigral inclusion body pathology and that it undergoes significant neuronal loss in PD (Brooks and Halliday ; Halliday, ; Henderson et al, ; Rüb et al, ; Truong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This classic view assumes that there is no structural damage to the thalamus itself. However, more recently, several studies revealed that the thalamus is one of select targets of extranigral inclusion body pathology and that it undergoes significant neuronal loss in PD Halliday, 2009;Henderson et al, 2000;R€ ub et al, 2002;Truong et al, 2009). Furthermore, recent views posit that the thalamus is more than just a relay for information coming from the basal ganglia and instead that it actively modulates the function of both the basal ganglia and cortical neurons (Halliday, 2009;Sherman, 2007).…”
Section: Thalamusmentioning
confidence: 99%
“…Evidence from postmortem human brain studies demonstrates that the CM/PF complex presents a 30 to 40% cell loss in PD [132134]. This thalamic degeneration appears to be specific to CM/PF because neighboring thalamic nuclei remain intact [133].…”
Section: How Does the Cm/pf-striatal System Degeneration Contributmentioning
confidence: 99%